FREQUENCY OF DIFFERENT RISK FACTORS ASSOCIATED WITH RECURRENT URINARY TRACT INFECTION AMONG POSTMENOPAUSAL WOMEN - Jameel, Sadia; Mahmud, Syed Nayer (Journal of Ayub Medical College Abbottabad, 2016)
Background: Urinary Tract Infection is one of the most common infections encountered by women. These infections have the tendency to recur. In order to identify women at risk of recurrence there is a need to identify risk factors associated with it. Among women, factors predisposing to recurrent infections are not much explored. The study was done with an objective to determine different risk factors associated with recurrent UTI among postmenopausal women. Methods: This was a cross sectional study conducted at the Out Patient Department of Nephrology in Shifa International Hospital Islamabad over a period of six months, June 6th to December 5th 2012. Information regarding demographics and risk factors were recorded on a predesigned pro forma. A descriptive analysis was done for quantitative variables like age and qualitative variables like marital status and frequency of different risk factors. Stratification of risk factors according to age was also done. Results: Hundred females were enrolled into the study after informed consent. The mean age of the study population was 64.4±9.48. 97% of the population was married. Out of 100 patients, 42 had high post-void volume, 35 had urinary incontinence and 17 patients were having cystocele. According to age stratification, most frequently affected age group was between 51-60 years (38%), followed by 61-70 years (36%), then 25% in more than 70 years, whereas only 1% was between 41-50 years. Conclusion: Recurrent UTI in postmenopausal females is most frequently associated with high post void volume and most frequently affected age group is between 51-60 years. Keywords: Recurrent UTI, Postmenopausal females, high post-void volume, cystocele, urinary incontinence